EARLY SETTLEMENTS AND PRECUREMENT OF RAW MATERIALS - NEW EVIDENCE BASED ON RESEARCH AT AKANTHOU-ARKOSYKOS (TATLISU- CIFTLIKDUZU), NORTHERN CYPRUS - Sevketoglu, Muege (Tuba-Turkish Acad Sciences, 2008)
[Abstract Not Available]
Keywords: Cyprus; Tatlisu- Ciftlikduzu/ Akanthou-Arkosykos; Aceramic Neolitik; obsidien; exchange; Anatolia